Inventaritation Of Endophyte Fungi from Avicennia Marina Leaves in Mempawah Mangrove Center, Pasir Village, Mempawah, West Borneo - Pesta Manurung, Lamria; Rahmawati, Rahmawati; Kurniatuhadi, Rikhsan (LenteraBio : Berkala Ilmiah Biologi, 2022)
Avicennia marina is a mangrove plant that grows on the coast of Pasir Village, Mempawah, West Borneo. Endophyte fungi are found in plant tissues and can function as agents for controlling pathogenic pests. The purpose of this study was to inventory the endophyte fungi that found in the leaf tissue of Avicennia marina at the Mempawah Mangrove Center in Pasir Village, Mempawah, West Borneo. This research was conducted from January 2019 to November 2020 at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. The method used in this research is pour plate method and fungal identification based on morphological characteristics. Based on the results of the study, four types of endophyte fungi were obtained from Avicennia marina leaves. The endophyte fungi found were Phytophtora, Cylindrocladium, Fusarium, and Mucor.